Pengaruh Penerapan Problem-Based Learning dalam Mata Kuliah Statistika terhadap Minat Mahasiswa Pendidikan Keagamaan Katolik untuk Melaksanakan Penelitian Kuantitatif - Varetha Lisarani (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2024)
This research examines the effect of implementing Problem-based Learning (PBL) in the Statistics course on the interest of Catholic Religious Education (CRE) prospective teachers students at the Sekolah Tinggi Agama Katolik Negeri Pontianak in conducting quantitative research. This study was conducted in response to the low interest of students in conducting quantitative research. In this study, student interest was measured using a 4-point Likert scale that reflects the highest phase of interest, which is well-developed individual interest. The results of the research show that the implementation of PBL in the Statistics course has a moderate impact on the interest of PKK students in conducting quantitative research. In the discussion, this research reveals that PBL encourages collaboration, concept understanding, and problem-solving together, which increases students' interest in conducting quantitative research. Furthermore, the research results also indicate that PBL makes the Statistics course more engaging and less boring for students who were previously hesitant about mathematics.